2021
DOI: 10.3390/ijms22189979
|View full text |Cite
|
Sign up to set email alerts
|

A Novel UPLC-MS/MS Method Identifies Organ-Specific Dipeptide Profiles

Abstract: Background: Amino acids have a central role in cell metabolism, and intracellular changes contribute to the pathogenesis of various diseases, while the role and specific organ distribution of dipeptides is largely unknown. Method: We established a sensitive, rapid and reliable UPLC-MS/MS method for quantification of 36 dipeptides. Dipeptide patterns were analyzed in brown and white adipose tissues, brain, eye, heart, kidney, liver, lung, muscle, sciatic nerve, pancreas, spleen and thymus, serum and urine of C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…Previous studies demonstrated LPS challenge caused alterations in lipid and protein metabolism in different animals ( Wan et al, 2017 ; Wang et al, 2017 ; Chirivi et al, 2022 ). In present study, taurolithocholic acid, myristoleic acid, stearoylcarnitine, PC (16:0/16:0), 1-Hexadecyl-sn-glycero-3-phosphocholine and Ser-Arg were significantly altered, suggesting that the abnormal degradation of lipid and protein were involved in the pathogenesis of stress in chicks ( Ozawa et al, 2020 ; Heidenreich et al, 2021 ). Therefore, the changed metabolites may explain the decreased growth performance of broilers with stress induced by LPS challenge.…”
Section: Discussionsupporting
confidence: 46%
“…Previous studies demonstrated LPS challenge caused alterations in lipid and protein metabolism in different animals ( Wan et al, 2017 ; Wang et al, 2017 ; Chirivi et al, 2022 ). In present study, taurolithocholic acid, myristoleic acid, stearoylcarnitine, PC (16:0/16:0), 1-Hexadecyl-sn-glycero-3-phosphocholine and Ser-Arg were significantly altered, suggesting that the abnormal degradation of lipid and protein were involved in the pathogenesis of stress in chicks ( Ozawa et al, 2020 ; Heidenreich et al, 2021 ). Therefore, the changed metabolites may explain the decreased growth performance of broilers with stress induced by LPS challenge.…”
Section: Discussionsupporting
confidence: 46%
“…We also uncover that N-acetylcarnosine is the primary circulating HCD in human plasma and is continuously secreted from skeletal muscle into the circulation, which is further increased by physical exercise. An overview of the main findings is visualized in Previous endeavors to profile HCDs mostly focused on rodent tissues, and resulted in fragmented and sometimes contradictory literature (13,(22)(23)(24)(25). Our systematic approach and very sensitive state-ofthe-art UHPLC-MS/MS methodology facilitate direct comparison between tissues and species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous endeavors to profile HCDs mostly focused on rodent tissues, and resulted in fragmented and sometimes contradictory literature ( 13, 2225 ). Our systematic approach and very sensitive state-of-the-art UHPLC-MS/MS methodology facilitate direct comparison between tissues and species.…”
Section: Discussionmentioning
confidence: 99%
“…This finding also emphasizes the importance of the brain's regional metabolomic analysis, as recent mapping of the regional distribution of dipeptides revealed particular localization patterns [47,48]. In addition, differential tissue distribution has been observed for isomeric dipeptides depending on the C-terminal amino acid [49].…”
Section: Discussionmentioning
confidence: 52%